Kinerja Pemerintah Desa Kondang Jaya Dalam Penyelenggaraan Pelayanan Publik Pada Bidang Administrasi - Hardiani Ikka Nur Prastiwi; Maulana Rifai; Kariena Febriantin (Jurnal Ilmiah Wahana Pendidikan, 2023)
Kondang Jaya Village is one of the villages in Karawang Regency. The purpose of compiling this research is to find out how the process of village administrative services in Kondang Jaya Village is running and to find out whether it is in accordance with village administrative service standards and to find out the problems that exist in the administration of village administration in providing services to the people of Kondang Jaya Village. This journal uses a qualitative approach to determine how to find, collect, process and analyze research data. From the results of field research, it can be concluded that in the administration of administrative services in Kondang Jaya Village, it has been going quite well, and the process has been running according to service standards, but the obstacles are from the community, who sometimes still don't accept if they want to make a letter no it could be because it does not comply with the regulations and also the lack of prowess on the part of some employees in handling and using computers.